Presence of Catholics People in Kendari amid Religious Plurality - Michael, Anthonius; Tandiangga, Patrio; Palinoan, Frans Fandy; Tandiarrang, Yulianti; Liling, Natalia Putri (Universitas Muhammadiyah Sorong, 2025)
The plurality of religions and beliefs is a reality of social life in Indonesia. Dealing with this reality requires an openness among adherents of religions and beliefs. It must be recognized that differences are like a double-edged sword. On the one hand, sometimes the differences can be a source of conflict, especially when dealing with conflicting interests. But on the other hand, plurality has positive potential, especially if the existing diversity can be managed properly so that it has the power to build public welfare. On this basis, the author tries to understand how Catholics continue to exist in Kendari's social life. The research method used in this study is a descriptive qualitative method, namely, participatory observation and interviews. This research shows that Catholics in Kendari, in addition to building a strong presence, also actively contribute to the social order, emphasizing unity, service, and collaboration in the context of the larger society. In addition, the research revealed obstacles to Catholic presence, such as new methods of evangelization, the reluctance of young people to get involved, and the growing shortage of Catholic educators. Therefore, there is a need for cooperation by embracing influential figures to maintain the presence and influence of the Catholic Church in society